Phenotypic changes of morphologically identified guinea-pig myenteric neurons following intestinal inflammation - Nurgali, Kulmira (Blackwell Science Inc, 2007)
We investigated the responses of morphologically identified myenteric neurons of the guinea-pig ileum to inflammation that was induced by the intraluminal injection of trinitrobenzene sulphonate, 6 or 7 days previously. Electrophysiological properties were examined with intracellular microelectrodes using in vitro preparations from the inflamed or control ileum. The neurons were injected with marker dyes during recording and later they were recovered for morphological examination. A proportion of neurons with Dogiel type I morphology, 45% (32/71), from the inflamed ileum had a changed phenotype. These neurons exhibited an action potential with a tetrodotoxin-resistant component, and a prolonged after-hyperpolarizing potential followed the action potential. Of the other 39 Dogiel type I neurons, no changes were observed in 36 and 3 had increased excitability. The afterhyperpolarizing potential (AHP) in Dogiel type I neurons was blocked by the intermediate conductance, Ca(2+)-dependent K(+) channel blocker TRAM-34. Neurons which showed these phenotypic changes had anally directed axonal projections. Neither a tetrodotoxin-resistant action potential nor an AHP was seen in Dogiel type I neurons from control preparations. Dogiel type II neurons retained their distinguishing AH phenotype, including an inflection on the falling phase of the action potential, an AHP and, in over 90% of neurons, an absence of fast excitatory transmission. However, they became hyperexcitable and exhibited anodal break action potentials, which, unlike control Dogiel type II neurons, were not all blocked by the h current (I(h)) antagonist Cs(+). It is concluded that inflammation selectively affects different classes of myenteric neurons and causes specific changes in their electrophysiological properties.